Burden of musculoskeletal-related disorders resulting from non-fatal road traffic collisions in Africa: a protocol of a systematic review. Issue 10 (28th October 2019) - Yusuf, Mohamed; Gebrye, Tadesse; Fatoye, Francis
Abstract : Introduction: In addition to their high mortality rates, road traffic collisions (RTC) are considered a burden within those who do survive. In Africa, injuries related to RTC have been identified as the 10th most common cause of disability-adjusted life years lost for all ages and categories. Moreover, non-fatal RTC are the biggest cause associated with the burden of musculoskeletal disorders (MSD) in Africa. Despite this, the epidemiology of MSD related to non-fatal RTC within this region is still unknown. The objective of this review is to identify and summarise available data regarding the prevalence, incidence and patterns of MSD resulting from non-fatal RTC in Africa. Methods and analysis: A systematic review of observational epidemiological studies will be conducted. On October 2019, MEDLINE, Embase, CINAHL Plus, PsycINFO, Web of Science, Global Health and African Journals OnLine will be searched for literature that is in English and published between 1990 and 2018. Two reviewers (MY ad TG) will independently screen results and extract the data, with a third reviewer (FF) resolving any discrepancies through discussion. Additionally, two reviewers (MY and TG) will independently assess the quality of the eligible studies using the US National Institutes of Health National Heart, Lung, and Blood Institute Quality Assessment Tool. Within the eligible studies, data on citation, methods and results will be extracted. Extracted data will be analysed using a narrative synthesis. Findings will be presented in tables, with the main outcomes being prevalence, incidence and disease pattern of MSD and determinants of non-fatal RTC. The final systematic review will be conducted as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline. Ethics and dissemination: As individual patients will not be involved in this study, no ethical approval will be sought. Findings from this review will be disseminated through peer-reviewed journals and relevant conferences. Trial registration number: CRD42019139538